Electrical and Photoresponse Properties of Inversion Asymmetric Topological Insulator BiTeCl Nanoplates. Issue 6 (2nd May 2017) - Liu, Yujing; Yin, Jianbo; Tan, Zhenjun; Wang, Mingzhan; Wu, Jinxiong; Liu, Zhongfan; Peng, Hailin
Abstract: Topological insulators (TIs) are new quantum materials with bulk energy gaps and unique helical gapless surface states protected by time‐reversal symmetry, providing a platform for the exploration of novel quantum phenomena and emerging applications. Bismuth tellurochloride (BiTeCl), the first strong inversion asymmetric topological insulator, has attracted considerable attention because of its exotic crystal structure and electrical band structure. Herein, we report the crystalline‐surface‐dependent n‐type and p‐type field effect transistors based on two‐dimensional (2D) BiTeCl nanoplates. The p‐type 2D BiTeCl exhibited a relatively strong photosensitivity with small dark current. Photovoltage generation in the vertical conducting channel of 2D BiTeCl is enhanced by 2–3 times in comparison with that in the planar conducting channel, presumably due to the enhanced separation efficiency of photogenerated electron–hole pairs induced by the existing built‐in electric field in polarized BiTeCl nanoplates. Our studies may encourage devoted efforts towards intrinsic topological p‐n junctions and high‐performance electrical and optoelectronic devices. Abstract : Light‐sensitive : BiTeCl, the first strong inversion asymmetric topological insulator, exhibits crystalline‐surface‐dependent band structure based on its 2D nanostructures. Larger photosensitivity was observed in the vertical conducting channel than the planar direction.